2020
DOI: 10.1371/journal.ppat.1008903
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection of African green monkeys results in mild respiratory disease discernible by PET/CT imaging and shedding of infectious virus from both respiratory and gastrointestinal tracts

Abstract: Vaccines are urgently needed to combat the global coronavirus disease 2019 (COVID-19) pandemic, and testing of candidate vaccines in an appropriate non-human primate (NHP) model is a critical step in the process. Infection of African green monkeys (AGM) with a low passage human isolate of SARS-CoV-2 by aerosol or mucosal exposure resulted in mild clinical infection with a transient decrease in lung tidal volume. Imaging with human clinicalgrade 18 F-fluoro-2-deoxy-D-glucose positron emission tomography (18 F-F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 42 publications
13
142
0
Order By: Relevance
“…This pattern is potentially linked to early innate immune responses that act within days, followed by adaptive responses that generally take one week to be activated. These observations are in line with recent findings that the presence of neutralizing serum antibodies in humans negatively correlates with infectious virus shedding, and that shedding of viral RNA outlasts shedding of infectious virus [ 17 ]. The presence of eosinophils in the nose and lungs of infected animals suggests a possible helper T cell 2 (Th2)-mediated immune response.…”
Section: Discussionsupporting
confidence: 90%
“…This pattern is potentially linked to early innate immune responses that act within days, followed by adaptive responses that generally take one week to be activated. These observations are in line with recent findings that the presence of neutralizing serum antibodies in humans negatively correlates with infectious virus shedding, and that shedding of viral RNA outlasts shedding of infectious virus [ 17 ]. The presence of eosinophils in the nose and lungs of infected animals suggests a possible helper T cell 2 (Th2)-mediated immune response.…”
Section: Discussionsupporting
confidence: 90%
“…Intrinsic species-specific susceptibility to disease progression has been described for NHP in SARS-CoV-1 6 with AGM being more susceptible than rhesus to severe disease. There were unexpected similarities in the kinetics and the quality of the immune responses analyzed in RM and AGM, particularly during the acute phase of infection, however, AGM did not clear the infection, as well as RM and two AGM, had the most severe symptoms 56 . While the number of animals enrolled in this study was not sufficient to look at species-specific differences and their effect on disease progression, we found that a higher ratio of IL-10: IL-6 in plasma was associated with disease severity.…”
Section: Discussionmentioning
confidence: 89%
“…Representatives of a number of animal species such as non-human primates 19 , dogs 20 , cats 20 , ferrets 20 , hamsters [21][22][23] , and bats 16 were susceptible to SARS-CoV-2 without prior species adaptation when infected experimentally. Natural infection has been documented for felines 24…”
Section: Discussionmentioning
confidence: 99%